The Enduring Pursuit: Land, Time and Social Relationships in Anthropological Models of Hunter-Gatherers and Hunters' Images - Feit, Harvey A. (Berg Publishers, 1994)
This paper examines recent models that have sought to characterize the distinctive features of hunter-gatherer societies that distinguish them from small-scale agricultural or pastoral societies. The survey also shows that hunter-gatherers are repeatedly portrayed as living in a distinctive temporal frame, one in which the juxtaposition of a lengthy past and an instantaneous present obviate an enduring present oriented to a future shaped by human agency. I consider these models in relation to some long-established and recent ethnographic and ethno-historic counter evidence, which I suggest has broad implications; and in relation to the cultural images crafted by subarctic Waswanipi Cree Indian hunters in Quebec. This survey concludes that there is no distinctive social feature of substance or consequence with which to distinguish hunter-gatherer societies. Social Sciences and Humanities Research Council of Canada, the McMaster University Arts Research Board, and the U.S. National Science Foundation for a conference travel grant.